SHAROF RASHIDOV’S ACTIVITIES AS CHAIRMAN OF THE PRESIDIUM OF THE SUPREME SOVIET OF THE UZBEK SSR (1950–1959) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the activities of the supreme governing body of the Uzbek SSR the Supreme Soviet during the 1950s. The author analyzes the sociopolitical work of Sharof Rashidov, who served as Chairman of the Presidium of the Supreme Soviet of the Uzbek SSR from 1950 to 1959. Special attention is given to the tensions in “Center Republic” relations and to the transformations in the sphere of state governance during the period under study.